First Do No Harm: Scientific Evidence Implicating Allopathic Vaccination - Miller, Neil Z. (Homœopathic Links, 2016)
Allopathic vaccination has many scientifically documented safety deficits that counteract well-publicised benefits. Thimerosal and aluminium, common ingredients in vaccines, can cause neurologic, immunologic and developmental harm. The pertussis vaccine has induced pertussis microorganisms associated with whooping cough to mutate and become more virulent. People vaccinated against pertussis can be asymptomatic carriers and transmitters of the disease, rendering herd immunity, or community immunity, unlikely. People vaccinated against measles can spread the disease to other fully vaccinated people. The MMR (measles-mumps-rubella) vaccine increases the probability of requiring emergency care. It also increases the risk of seizures and thrombocytopenia, a serious bleeding disorder. Infections experienced during childhood, such as measles, mumps and chickenpox, encourage normal development of the immune system in most children, offering protection against heart disease, strokes and cancer in adulthood. Vaccines—which are designed to prevent infections—increase cancer rates.
Keywords: vaccination; immunisation; thimerosal; pertussis; measles; MMR vaccine